The action-sentence compatibility effect in third person action sentence comprehension - Cai, Zhiwei; Qi, Bing; Fan, Ning (Frontiers in Psychology, 2025)
This study investigates the influence of object animacy and perspective priming on the Action-sentence Compatibility Effect (ACE) in third-person action sentences using the sentence sensibility judgment paradigm. Experiment 1 showed that ACE occurred along the front-back axis when the object was an inanimate noun. Experiment 2 revealed that ACE appeared along the left–right axis when the object was a personal name. Experiment 3 demonstrated that ACE aligned with the action’s direction under agent priming, while ACE shifted to the opposite direction under patient priming. These findings suggest that participants can flexibly simulate the perspective of an action based on spatial when processing third-person action sentences.